Vaginal Myomectomy for a Thirteen-Centimeter Anterior Myoma. (10th April 2013) - Deval, Bruno; Rousset, Pascal; Kayani, Salma
Abstract : Vaginal myomectomy is an uncommon but advantageous approach for large interstitial uterine fibroids. Myomectomy is performed via laparotomy and laparoscopy; however, in selected cases, vaginal myomectomy has been proven to be a safe and an effective surgical procedure. We report the case of a 38-year-old para one woman with complaints of chronic lower abdominal pain. Preoperative workup revealed a thirteen-centimeter interstitial uterine myoma in the anterior wall. Successful myomectomy was performed via the vaginal route. We will share the preoperative images, operative technique, and postoperative images.